2022
DOI: 10.3389/fenvs.2022.963145
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdown on the ambient air-pollutants over the Arabian Peninsula

Abstract: Lockdowns imposed across the world to combat the spread of the COVID-19 pandemic also reduced the anthropogenic emissions. This study investigates the changes in the anthropogenic and natural pollution levels during the lockdown over the Arabian Peninsula (AP), a region where natural pollutants (mineral dust) dominate. In-situ and satellite observations, reanalysis products, and Weather Research and Forecasting model (WRF) coupled with Chemistry module (WRF-Chem) simulations were analyzed to investigate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Studies in Brazil observed a reduction of NO 2 (− 54.3%), CO (− 64.8%) and an increase in O 3 (30%) (Nakada & Urban, 2020 ) . Karumuri et al ( 2022 ) also found similar reduction (50–60%) in NO 2 and SO 2 over Arabian Peninsular using WRF-Chem model simulations.…”
Section: Introductionmentioning
confidence: 61%
“…Studies in Brazil observed a reduction of NO 2 (− 54.3%), CO (− 64.8%) and an increase in O 3 (30%) (Nakada & Urban, 2020 ) . Karumuri et al ( 2022 ) also found similar reduction (50–60%) in NO 2 and SO 2 over Arabian Peninsular using WRF-Chem model simulations.…”
Section: Introductionmentioning
confidence: 61%
“…Karagulian et al, (2019) highlighted the effectiveness of integrating WRF-chem model simulations with satellite and ground observations to understand and predict the impact of severe dust storms on air quality. Karumuri et al, (2022) reported significant air quality changes due to COVID-19 lockdown measures, with reduced trace gas concentrations but increased particulate matter from dust activities, the latter stressed by Francis et al (2022a) who attributed it to changes in the atmospheric circulation. Moreover, Parajuli et al, (2022; utilized high-resolution WRF-Chem simulations and advanced aerosol schemes to analyse the dust and rainfall dynamics, providing insights into the direct and indirect effects of dust on rainfall which aids in better regional water resource planning through accurate rainfall predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Dust activity over the AP typically begins in early spring and peaks in summer (e.g., Kunchala et al, 2018), although occasional dust events occur throughout the year. The abrupt increase in summer dust emissions over the AP is due to enhanced local surface heating, strong local winds, and a reduction in soil moisture and vegetation (e.g., Davis et al, 2015;Karumuri et al, 2021Karumuri et al, , 2022Kunchala et al, 2019;Yu et al, 2016). The seasonal and interannual variability of dust accumulation over the AP is closely associated with the frequency and intensity of dust storms (Farahat et al, 2015).…”
Section: Introductionmentioning
confidence: 99%